2014
DOI: 10.1186/s40478-014-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of different types of multiple sclerosis lesions yields FGF1 as a promoter of remyelination

Abstract: Chronic demyelination is a pathological hallmark of multiple sclerosis (MS). Only a minority of MS lesions remyelinates completely. Enhancing remyelination is, therefore, a major aim of future MS therapies. Here we took a novel approach to identify factors that may inhibit or support endogenous remyelination in MS. We dissected remyelinated, demyelinated active, and demyelinated inactive white matter MS lesions, and compared transcript levels of myelination and inflammation-related genes using quantitative PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 80 publications
2
56
1
Order By: Relevance
“…A study by Mohan et al (111) suggest that CXCL8 and LIF are involved in the protective effects of FGF1: in a comparative screening of remyelinated and unmyelinated chronic MS lesions, the authors identified FGF1 as an putative inductor of remyelination. This hypothesis was further tested in vitro , when exposure of myelinating and organotypic cerebellar cultures showed enhanced myelination upon exposure to FGF1.…”
Section: Chemokines Secreted By Astrocytesmentioning
confidence: 99%
“…A study by Mohan et al (111) suggest that CXCL8 and LIF are involved in the protective effects of FGF1: in a comparative screening of remyelinated and unmyelinated chronic MS lesions, the authors identified FGF1 as an putative inductor of remyelination. This hypothesis was further tested in vitro , when exposure of myelinating and organotypic cerebellar cultures showed enhanced myelination upon exposure to FGF1.…”
Section: Chemokines Secreted By Astrocytesmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic autoimmune disease characterized by localized destruction of the myelin sheets that enwrap and support axons of the central nervous system (CNS) (Friese et al, 2014; Mohan et al, 2014). The etiology is unknown and a satisfactory cure is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its developmental regulation, the expression of LINGO-1 was found upregulated upon CNS injury as shown in spinal cord injury and human MS (Mi et al, 2004; Mohan et al, 2014; Satoh et al, 2007). There seems to be, however, some controversy on whether this upregulation occurs primarily on cells of the OLG lineage or in subpopulations of reactive astrocytes, macrophages/microglia and neurons (Satoh et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…With regard to potential detrimental roles, injection of FGF-2 into the lateral ventricles of postnatal mice was found to delay myelination and lead to myelin breakdown (Goddard et al, 2001, 1999), and genetic deletion of Fgf2 or FGFR1 resulted in improved remyelination following experimental demyelination (Mierzwa et al, 2013; Tobin et al, 2011; Zhou et al, 2012). Conversely, however, FGF signaling has also been associated with successful remyelination (Mohan et al, 2014) and been described to potentiate myelin repair (Dehghan et al, 2012), provide neuroprotection (Rottlaender et al, 2011) and ameliorate clinical signs in a chronic EAE model (Ruffini et al, 2001). Recent data revealed that conditional deletion of both FGFR1 and FGFR2 in cells of the OLG lineage does not affect remyelination following acute myelination, but impairs OLG differentiation and/or survival in chronically demyelinated lesion, suggesting that cell-autonomous FGF signaling in OLGs is redundant during recovery of acute demyelinated lesions, but may facilitate regenerative processes in chronic demyelination (Furusho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%